Nilai-nilai Etos Kerja Islam pada Jamaah Majelis Doa dan Taklim At-Taqwa Wonokromo Pleret Bantul - Siswoyo Aris Munandar; Hartatik Febri Purwanti; Laelatul Barokah (IAIN Palangka Raya, 2020)
This study attempted to determine the value of the Islamic work ethic of At-Taqwa Wonokromo Pleret Bantul prayer groups and taklim prayer groups after attending the Fatihah zikr. This study belonged to qualitative with a phenomenological approach. Data were collected in three ways, namely observation, interviews, and documentation. The finding revealed that consistency on practicing zikr can contribute to the establishing and strengthening the work ethic of each individual. At this level the Al-Fatihah zikr practiced by the followers of At-taqwa prayer group influenced for increasing the work ethic of the followers of the Fatihah zikr. Specifically there were six values of the Islamic work ethic existed, namely working for worship, responsibility for work, motivation at work, always grateful for favors, optimism and positive thinking, and sincere values.Keyword : Work Ethic, Zikr, Al-Fatihah.